Mobilize to vaccinate: lessons learned from social mobilization for immunization in low and middle-income countries. Issue 5 (3rd May 2020) - Jalloh, Mohamed F.; Wilhelm, Elisabeth; Abad, Neetu; Prybylski, Dimitri
ABSTRACT: Creating and sustaining demand for immunization services is a global priority to ensure that vaccine-eligible populations are fully protected from vaccine-preventable diseases. Social mobilization remains a key health promotion strategy used by low- and middle-income countries (LMICs) to promote vaccination demand. In this commentary, we synthesize illustrative evidence on successful social mobilization efforts promoting the uptake of immunization services in select LMICs. The first example focuses on Sierra Leone's routine immunization program during the Universal Child Immunization initiative in the late 1980s. We then give an example of India's establishment of a social mobilization network in the early- to mid-2000s to support polio elimination in high-risk communities. Thirdly, we highlight the complexities of social mobilization in a humanitarian emergency during the 2017–2018 diphtheria outbreak among displaced Rohingyas in camps and settlements in Bangladesh. Lastly, we draw upon examples from the introduction of the human papillomavirus vaccine in several countries. We then critically examine recurring challenges faced when implementing social mobilization for immunization in LMICs and offer practical recommendations for improvement.